Two dimensional quantum mechanical simulation of low dimensional tunneling devices. (November 2015) - Alper, C.; Palestri, P.; Lattanzio, L.; Padilla, J.L.; Ionescu, A.M.
Abstract: We present a 2-D quantum mechanical simulation framework based on self-consistent solutions of the Schrödinger and Poisson equations, using the Finite Element Method followed by tunneling current (direct and phonon assisted) calculation in post-processing. The quantum mechanical model is applied to Germanium electron–hole bilayer tunnel FETs (EHBTFET). It is found that 2D direct tunneling through the underlap regions may degrade the subthreshold characteristic of such devices and requires careful device optimization to make the tunneling in the overlap region dominate over the parasitic paths. It is found that OFF and ON state currents for the EHBTFET can be classified as point and line tunneling respectively. Oxide thickness was found to have little impact on the magnitude of the ON current, whereas it impacts the OFF current.